2006
DOI: 10.1016/j.jmps.2006.03.001
|View full text |Cite
|
Sign up to set email alerts
|

Non-slipping adhesive contact between mismatched elastic spheres: A model of adhesion mediated deformation sensor

Abstract: A generalized JKR model is established for non-slipping adhesive contact between two dissimilar elastic spheres subjected to a pair of pulling forces and a mismatch strain. We discuss the full elastic solution to the problem as well as the so-called non-oscillatory solution in which tension and shear tractions along the contact interface is decoupled from each other. The model indicates that the mismatch strain has significant effect on the contact area and the pull-off process. Under a finite pulling force, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
27
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 57 publications
6
27
0
Order By: Relevance
“…Previous researches have shown, both theoretically and experimentally, that a uniform elastic strain imposed on a substrate tends to reduce the contact area of a particle adhering on a substrate [30][31][32][33][34][35][36]. In the present experiment, the strain field in the elastic layer is highly non-uniform across the tip of the interface crack.…”
Section: (B)mentioning
confidence: 58%
See 1 more Smart Citation
“…Previous researches have shown, both theoretically and experimentally, that a uniform elastic strain imposed on a substrate tends to reduce the contact area of a particle adhering on a substrate [30][31][32][33][34][35][36]. In the present experiment, the strain field in the elastic layer is highly non-uniform across the tip of the interface crack.…”
Section: (B)mentioning
confidence: 58%
“…Therefore, in the absence of a strain gradient, there can be membrane detachment [30][31][32][33][34][35][36] but no subsequent directional motion. The average strain in the substrate can only affect G init , hence the initiation of a detachment, but it has no effect on the steady state energy release rate G ss which is necessary for the observed directional motion.…”
Section: The Steady State Rollingmentioning
confidence: 99%
“…The adhesive contact mechanics represented by JKR and DMT models has triggered extensive research effort over the past three decades (Muller et al, 1980;Greenwood and Johnson, 1981;Barquins, 1988;Carpick et al, 1996;Chaudhury et al, 1996;Baney and Hui, 1997;Greenwood, 1997;Johnson and Greenwood, 1997;Barthel, 1998;Greenwood and Johnson, 1998;Kim et al, 1998;Morrow et al, 2003;Chen and Gao, 2006a, 2006b, 2007a, 2007b. In recent years, it is also becoming a valuable platform to study biological adhesion systems such as cell-cell contact (Chu et al, 2005;Chen and Gao, 2006b), cells on stretched substrates (Chen and Gao, 2006a), as well as adhesion systems of gecko and insects (Autumn and Peattie, 2002;Artz et al, 2003;Glassmaker et al, 2004;Hui et al, 2004;Gao et al, 2005;Spolenak et al, 2005;Yao, 2006;Yao andGao, 2006, 2007;Chen and Gao, 2007a;Chen and Soh, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, it is also becoming a valuable platform to study biological adhesion systems such as cell-cell contact (Chu et al, 2005;Chen and Gao, 2006b), cells on stretched substrates (Chen and Gao, 2006a), as well as adhesion systems of gecko and insects (Autumn and Peattie, 2002;Artz et al, 2003;Glassmaker et al, 2004;Hui et al, 2004;Gao et al, 2005;Spolenak et al, 2005;Yao, 2006;Yao andGao, 2006, 2007;Chen and Gao, 2007a;Chen and Soh, 2008). Among these studies, Yao (2006) and considered an interfacial crack model and showed that graded elastic materials can promote robust adhesion.…”
Section: Introductionmentioning
confidence: 99%
“…Recent interest in bio-inspired adhesives has motivated many researchers to fabricate microfibril arrays (Liu & Bhushan 2003;Peressadko & Gorb 2004;Chung & Chaudhury 2005;Crosby et al 2005;Glassmaker et al 2005Glassmaker et al , 2007Huber et al 2005;Northen & Turner 2005;Yurdumakan et al 2005;Kim & Sitti 2006;Majidi et al 2006;Aksak et al 2007;Gorb et al 2007;Greiner et al 2007; and to study their contact mechanics and adhesion (Jagota & Bennison 2002;Gao et al 2003Gao et al , 2005Persson & Gorb 2003;Hui et al 2004;Persson et al 2005;Spolenak et al 2005a,b;Tang et al 2005;Bhushan et al 2006;Tian et al 2006;Yao & Gao 2006;Chen & Gao 2007). Most of these studies focus on how the interface between the microfibrils and a smooth, hard substrate separates under a normal load.…”
Section: Introductionmentioning
confidence: 99%